Children and adolescents’ singing in everyday life and at school - Boal-Palheiros, G. (2018)
Extensive research has shown the numerous benefits of singing and overall engagement in music for the intellectual, social, personal and musical development of children and young people (Hallam, 2010; Welch et al, 2010). Previous studies on singing in everyday life and at school suggest that young people actively engage in singing in and out of school. Although they enjoy it in both contexts, some adolescents dislike singing at school because they feel uncomfortable when being exposed and stressed when they are evaluated in singing tests or competitions (Mito & Boal-Palheiros, 2012; 2013). A number of studies in various countries showed the students’ low interest for school music and for school singing in particular (Boal-Palheiros & Hargreaves, 2001; Kobayashi, 2004). We need to investigate the possible gap between singing in everyday life and at school and how these contexts relate to each other in order to understand the impact of singing in children and adolescents’ lives.